Value of ultrasonography in the diagnosis of gout in patients presenting with acute arthritis - Nuttaya Pattamapaspong (2018)
© 2017, ISS. Objective: To evaluate the value of ultrasonographic features of crystal deposition for diagnosing gout in patients presenting with acute arthritis. Materials and methods: Ultrasound scanning of the most inflamed joint was performed on 89 consecutively enrolled patients with acute arthritis. Two radiologists independently reviewed the ultrasound images, and a consensus was achieved with a third radiologist when the interpretations of four key ultrasound features of gout differed. Arthrocentesis and crystal analysis using compensated polarized light microscopy of aspirates are considered the gold standards for gout diagnosis. Results: Fifty-three (60%) patients had gout, whereas the remaining 36 (40%) had non-gout arthritis. The mean serum uric acid level was 7.1 mg/dl in patients with gout and 4.7 mg/dl in patients with non-gout arthritis. Three US features differed significantly (p < 0.001) between patients with gout and non-gout arthritis: the double contour sign (42 vs. 8%, respectively), intra-articular aggregates (58 vs. 8%), and tophi (40 vs. 0%). No statistically significant differences in detecting intra-tendinous aggregates (32 vs. 17%, p = 0.14) were observed. The sensitivity and specificity of the double contour sign were 42 and 92%, respectively; those of the intra-articular aggregates were 58 and 92%; and those of tophi were 40 and 100%. The positive predictive values for these three features ranged from 88 to 100%, whereas the negative predictive values ranged from 52 to 60%. Conclusions: When the prevalence is high, these three ultrasound features may be a useful adjunct in the diagnosis of acute gout, particularly when specialized microscopic techniques are not available.